Cutting Metal Sheet with a Punch with Internal Heating - Jan Moravec (Communications - Scientific letters of the University of Zilina, 2018)
This paper describes issues related to the process of cutting with a punch with internal heating. The theoretical part explains the effects related to thermal expansion, conduction and transfer of heat in the body of punches. The experimental part refers to the design of a tool with an internally heated punch. Experimental results are summarised and the process is analysed in the discussion.